Sleep Disturbance Induces Increased Cholesterol Level by NR1D1 Mediated CYP7A1 Inhibition - Xing, Chen; Huang, Xin; Zhang, Yifan; Zhang, Chongchong; Wang, Wei; Wu, Lin; Ding, Mengnan; Zhang, Min; Song, Lun (Frontiers in Genetics, 2020)
Disturbed sleep is closely associated with an increased risk of metabolic diseases. However, the underlying mechanisms of circadian clock genes linking sleep and lipid profile abnormalities have not been fully elucidated. This study aimed to explore the important role of the circadian clock in regulating impaired cholesterol metabolism at an early stage of sleep deprivation (SD). Sleep disturbance was conducted using an SD instrument. Our results showed that SD increased the serum cholesterol levels. Concentrations of serum leptin and resistin were much lower after SD, but other metabolic hormone concentrations (adiponectin, glucagon, insulin, thyroxine, norepinephrine, and epinephrine) were unchanged before and after SD. Warning signs of cardiovascular diseases (decreased HDL-cholesterol and increased corticosterone and 8-hydroxyguanosine levels) and hepatic cholestasis (elevated total bile acids and bilirubin levels) were observed after SD. Cholesterol accumulation was also observed in the liver after SD. The expression levels of HMGCR, the critical enzyme for cholesterol synthesis, remained unchanged in the liver. However, the expression levels of liver CYP7A1, the enzyme responsible for the conversion of cholesterol into bile acids, significantly reduced after SD. Furthermore, expression of NR1D1, a circadian oscillator and transcriptional regulator of CYP7A1, strikingly decreased after SD. Moreover, NR1D1 deficiency decreased liver CYP7A1 levels, and SD could exacerbate the reduction of CYP7A1 expression in NR1D1-/- mouse livers. Additionally, NR1D1 deficiency could further increase serum cholesterol levels under SD. These results suggest that sleep disturbance can induce increased serum cholesterol levels and liver cholesterol accumulation by NR1D1mediated CYP7A1 inhibition.